Physicochemical quality assessment of four asparaginases - Vanessa Radtke; Thorsten König; Christoph Radcke; Ulf Bergmann; Rene Eichler; Katja J. Pohl; Arndt Schnuchel (PLoS ONE, 2025)
L-Asparaginases (ASNases) are used for the treatment of acute lymphoblastic leukaemia. There are reports of quality problems for some therapeutic asparaginase products, especially those manufactured in middle-income countries. These products may exhibit decreased potency and/or decreased specific activity, or an elevated level of impurities such as host cell proteins. In this study, four different ASNase preparations that were not modified with polyethylene glycol were compared in detail regarding their quality: Spectrila®, Celginase™, Bionase®, and L-Aspase®. Samples were analyzed for protein content, impurities, and enzyme activity. Various chromatographic methods as well as mass spectrometry were used to assess purity and identity. Sample protein content, host cell protein, and enzyme activity showed some results that were out of target range for Celginase™ and Bionase®. These ASNase preparations also showed detectable levels of endotoxins. In gel electrophoresis, additional bands were found for Bionase®. Size exclusion chromatography showed increased high and low molecular weight species for Bionase® and L-Aspase®, and reversed-phase chromatography showed increased hydrophilic and hydrophobic species for Bionase®. In capillary zone electrophoresis, increased retention time for L-Aspase® and increased levels of charge variants for Bionase®, Celginase™, and L-Aspase® were seen. ASNase quality standards are crucial to ensure patient safety and product efficacy, as decreased potency and specific activity may affect efficacy in acute lymphoblastic leukaemia treatment, and increased impurities may affect immunogenicity. Out of four ASNase preparations tested in this study, only Spectrila® did not raise any quality concerns. The other three products exhibited quality problems, rendering them unsuitable according to established quality requirements defined in European and US guidelines for pharmaceutical development of parenteral drug products.